Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/ep.10385
|View full text |Cite
|
Sign up to set email alerts
|

Thermal pretreatment of lignocellulosic biomass

Abstract: Torrefaction is a process to convert diverse lignocellulosic biomass feedstocks into an energy dense homogeneous solid, a pretreatment for subsequent thermochemical conversion. Loblolly pine was treated by wet torrefaction (hot compressed water, 200-2608C) and dry torrefaction (nitrogen, 250-3008C), with mass yield of solid product ranging between 57 and 89%, and energy densification to 108-136% of the original feedstock. The solid product has been characterized, including proximate analysis, fiber analysis, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
215
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(244 citation statements)
references
References 15 publications
22
215
1
3
Order By: Relevance
“…The thermal pretreatment, which mainly refers to the torrefaction process, can be divided into a dry and wet (hydrothermal) torrefaction (Yan et al, 2009). Table 3 gives different characteristics of the wet and dry torrefaction.…”
Section: Thermalmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal pretreatment, which mainly refers to the torrefaction process, can be divided into a dry and wet (hydrothermal) torrefaction (Yan et al, 2009). Table 3 gives different characteristics of the wet and dry torrefaction.…”
Section: Thermalmentioning
confidence: 99%
“…The torrefaction of biomass destructs the tenacity and fibrous structure of the biomass, and also increases its energy density. Numerous studies concluded that the torrefied biomass can avoid many limitations associated with the raw biomass because it produces moisture free hydrophobic solid products (Acharjee et al, 2011), decreases O/C ratio , reduces grinding energy (Repellin et al, 2010;Phanphanich and Mani, 2011), enhances energy density (Yan et al, 2009), increases bulk density and simplifies storage and transportation (Bergman, 2005;Phanphanich and Mani, 2011), improves particle size distribution (Phanphanich and Mani, 2011), intensifies combustion with less smoke (Pentananunt et al,1990), shifts combustion zone to the high temperature zone in a gasifier (Ge et al, 2013), and increases the resistance to the biological decay (Chaouch et al, 2010). Many of these improvements make the torrefied biomass more suitable than the raw biomass for co-firing in the conventional coal power plants, with minor modifications (Clausen et al, 2010).…”
Section: Motivations For Torrefactionmentioning
confidence: 99%
“…Cross-links are formed when hydroxyl groups are removed during dehydration reactions. Adjacent cross-links form stable compounds that appear as lignin in the fibre analysis; therefore, the degree of cross-linking can be determined by the increase in acid insoluble fibres during biomass hydrolysis [47,49].…”
Section: Torrefactionmentioning
confidence: 99%
“…Adicionalmente, o briquete é convertido em um combustível com maior poder calorífico, menor teor de materiais voláteis, maior teor de carbono fixo, uniformidade em forma e tamanho, menor relação O/C e baixa umidade (Shafizadeh, 1985;Felfli et al, 2005;Prins et al, 2006;Yan et al, 2009;Chen et al, 2011).…”
Section: Introductionunclassified